Kolaborasi Pelaku Usaha Dalam Praktik Non Harga Perspektif Hukum Ekonomi Syariah - Asmaliah, Fifin; Aswan, Aswan; Jeri, Ahmat; Anugrah, Aril (Fawaid : Sharia Economic Law Review, 2025)
This study explores the collaboration among entrepreneurs in the realm of non-price practices from the perspective of Islamic economic law. It focuses on the prohibitions of iktikhar and tadlis, which are considered unethical and detrimental to the integrity of business transactions. Iktikhar involves deceptive practices that mislead consumers, while tadlis refers to concealing defects or flaws in products. Both practices undermine consumer trust and threaten the sustainability of partnerships among entrepreneurs. Through a qualitative analysis, this research highlights the importance of ethical behavior in fostering a business environment that values transparency and mutual benefit. The findings suggest that adherence to Islamic ethical standards not only enhances the reputation of collaborative ventures but also contributes to the long-term success of businesses. By promoting ethical practices in non-price competition, this study provides insights into the potential for creating sustainable business relationships rooted in integrity, ultimately leading to a more equitable and trustworthy marketplace. Keywords: Non-price practices,Iktikhar,Tadlis